Thermo-diffusion and Diffusion-thermo Effects on Free Convection Heat and Mass Transfer from Vertical Surface in a Porous Medium with Viscous Dissipation in the Presence of Thermal Radiation - , G. Sreedhar Sarma; , K. Govardhan (Archives of Current Research International, 2015)
The finite difference method is employed to examine free convective heat and mass transfer in a steady two-dimensional fluid flow from vertical surface in porous medium. In this study thermal radiation, viscous dissipation and Soret, Dufour effects are taken into consideration. The two-dimensional boundary-layer governing partial differential equations have been transformed by a similarity transformation into a system of ordinary differential equations which are solved numerically. The effects of different involved parameters such as Lewis number, Soret number, thermal radiation and viscous dissipation parameter on velocity, temperature and concentration profiles are plotted and discussed in the paper.